2021
DOI: 10.3389/fneur.2021.715618
|View full text |Cite
|
Sign up to set email alerts
|

Increased Sodium Concentration in Substantia Nigra in Early Parkinson's Disease: A Preliminary Study With Ultra-High Field (7T) MRI

Abstract: Pathophysiology of idiopathic Parkinson's disease (iPD) is complex and still misunderstood. At a time when treatments with disease-modifying potential are being developed, identification of early markers of neurodegeneration is essential. Intracerebral sodium accumulation could be one of them. Indeed, it may be in relation to the mitochondrial dysfunction that early exists in iPD. For the first time, we used brain sodium (23Na) MRI to explore sodium concentration changes that have already been reported to be r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In a recent study applying high-field 23 Na-MRI, similar changes were demonstrated in the midbrain of patients with Parkinson’s disease. Comparative studies are therefore needed to investigate whether observed changes are specific to distinct Parkinsonian disorders [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study applying high-field 23 Na-MRI, similar changes were demonstrated in the midbrain of patients with Parkinson’s disease. Comparative studies are therefore needed to investigate whether observed changes are specific to distinct Parkinsonian disorders [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides some disadvantages, 23 Na-MRI will provide deepened insights into specific disease mechanisms and can help in complimentary map neurodegeneration in vivo. However, the combination with other, in particular pathophysiology-orientated, neuroimaging modalities would be desirable to further enhance the biological interpretability of our findings [ 13 ]. Future studies in larger cohorts are necessary to ensure the reproducibility of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…The 23 Na-MRI data were processed according to (Grimaldi et al, 2021) using a homemade adjusted procedure. After brain extraction on ²³Na-MRI images (ANTS, (Avants et al, 2011)), a denoising filter was applied to the resulting 23 Na-MRI volumes (Aja-Fernandez et al, 2008; Rajan et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Patients with AD have also shown a significant increase in the tissue sodium Figure 6. Brain disorders exhibiting abnormal sodium concentration levels during 23 Na imaging with the disease progression including AD, 77,82 brain tumor, 42,83 epilepsy, 84 MS, 85 cerebral ischemia 86 Friedreich's ataxia, 87 Huntington's disease, 88 glioblastoma, 89 Parkinson's disease, 90 stroke, 91 migraine, 92 and cerebral hemorrhage. volume in the amygdala, hippocampus, and WM as compared to healthy controls, which denotes neuronal loss.…”
Section: ■ Sodium Mri Applicationsmentioning
confidence: 99%
“…Brain disorders exhibiting abnormal sodium concentration levels during 23 Na imaging with the disease progression including AD, , brain tumor, , epilepsy, MS, cerebral ischemia Friedreich’s ataxia, Huntington’s disease, glioblastoma, Parkinson’s disease, stroke, migraine, and cerebral hemorrhage …”
Section: Sodium Mri Applicationsmentioning
confidence: 99%